Labensphilosophie on the essence of humanity. Anthropological motifs in philosophy of Henri Bergson - Ples, Marta (Folia Philosophica, 2011)
The paper deals with the philosophy of Henri Bergson (1859-1941) taken from the perspective of anthropological themes it contains. The aim of the paper is to point out in what way in Bergson’s theory two dimensions of humanity are interlinked. On the one hand, the man is presented as social being, creating smaller or larger social structures naturally and doomed to believe in what is irrational in equally natural way. On the other hand, Bergson raises a question about the basis of personality and consciousness of individual, and in relation with the broad framework of his theory of lasting, he takes every man as related in the very heart of his being with the whole world around.